RESULTS OF IMPORT SUBSTITUTION ANALYSIS OF ANTI-CANCER MEDICATIONS IN THE RUSSIAN FEDERATION (2013–2018) - O. A. Ryzhova; T. L. Moroz (Фармация и фармакология (Пятигорск))
The aim. Due to the social importance of anticancer drugs, the aim of the study is to conduct a comparative analysis of the range of domestic and foreign anticancer medications included in the Lists of Vital and Essential Drugs in 2013 and 2018 in the aspect of import substitution.Materials and methods. The study was conducted by comparing the data on the registered anticancer preparations included in the list of Vital and Essential Drugs in the State Register of Medicines in 2013 and 2018. Statistical processing of the data was carried out on the basis of Fisher Z-test method.Results. All in all, there were 286 trade names of anticancer drugs registered in the Russian Federation in 2013. 94 of them, i.e. 33%, were Russian-made. In 2013, there were 19 pharmaceutical substances of domestic production in the analyzed group, which accounted for 27% of 71 INNs (International nonproprietary name). As for 71 INNs, in 2018 there were 393 registered trade names of anticancer drugs. 162 drugs, i.e. 41%, were Russian-made. From 2013 to 2018, a statistically significant positive trend of the increase in the number of domestic anticancer drugs by 8% was revealed.Conclusion. In order to increase the volume of import substitution in the production of anticancer drugs, it is necessary to provide state support to Russian manufacturers, who register domestic analogues for the first time. A particular attention should be paid to the production of domestic pharmaceutical substances, without which it is impossible to ensure the drug safety of the country.